Frictional Heating Processes and Energy Budget During Laboratory Earthquakes. Issue 22 (28th November 2018) - Aubry, J.; Passelègue, F. X.; Deldicque, D.; Girault, F.; Marty, S.; Lahfid, A.; Bhat, H. S.; Escartin, J.; Schubnel, A.
Abstract: During an earthquake, part of the released elastic strain energy is dissipated within the slip zone by frictional and fracturing processes, the rest being radiated away via elastic waves. While frictional heating plays a key role in the energy budget of earthquakes, it could not be resolved by seismological data up to now. Here we investigate the dynamics of laboratory earthquakes by measuring frictional heat dissipated during the propagation of shear instabilities at stress conditions typical of seismogenic depths. We estimate the complete energy budget of earthquake rupture and demonstrate that the radiation efficiency increases with thermal‐frictional weakening. Using carbon properties and Raman spectroscopy, we map spatial heat heterogeneities on the fault surface. We show that an increase in fault strength corresponds to a transition from a weak fault with multiple strong asperities and little overall radiation, to a highly radiative fault behaving as a single strong asperity. Plain Language Summary: In nature, earthquakes occur when the stress accumulated in a medium is released by frictional sliding on faults. The stress released is dissipated into fracture and heat energy or radiated through seismic waves. The seismic efficiency of an earthquake is a measure of the fraction of the energy that is radiated away into the host medium. Because faults are at inaccessible depths, we reproduce earthquakes in the laboratory under natural in situ conditions to understand the physical processes leading to dynamic rupture. We estimate the first complete energy budget of an earthquake and show that increasing heat dissipation on the fault increases the radiation efficiency. We develop a novel method to illuminate areas of the fault that get excessively heated up. We finally introduce the concept of spontaneously developing heat asperities, playing a major role in the radiation of seismic waves during an earthquake. Key Points: Spatial heat heterogeneities are imaged on a frictional interface using carbon properties and Raman spectroscopy Rupture processes become more efficient with increasing slip on fault Heating efficiency depends on time‐dependent memory effect of the fault surface